2009
DOI: 10.1542/peds.2008-1290
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Disclosure of HIV Infection on Health-Related Quality of Life Among Children and Adolescents With HIV Infection

Abstract: Background-Little is known concerning the impact of HIV status disclosure on quality of life, leaving clinicians and families to rely on research of children with other terminal illnesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
86
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 29 publications
(32 reference statements)
13
86
0
1
Order By: Relevance
“…Increasingly, clinicians now address issues of disclosure at an earlier age than previously 99, with awareness that early, general discussions focusing on healthy diet and lifestyle and knowledge about the blood and immune system can provide a useful foundation for later, specific discussions about HIV. It will generally be appropriate for most children to know their HIV status (i.e.…”
Section: Adherence and Hiv Knowledgementioning
confidence: 99%
“…Increasingly, clinicians now address issues of disclosure at an earlier age than previously 99, with awareness that early, general discussions focusing on healthy diet and lifestyle and knowledge about the blood and immune system can provide a useful foundation for later, specific discussions about HIV. It will generally be appropriate for most children to know their HIV status (i.e.…”
Section: Adherence and Hiv Knowledgementioning
confidence: 99%
“…The raw scores in all seven domains had different minimum and maximum values, therefore, the raw scores were calculated to simple transformed scores of 0 to 100 with the following formula: transformed score = [(actual raw score -lowest possible raw score)/ (highest possible raw score -lowest possible raw score)] · 100]. 3,10,13,19 For items with mixed or negative directionality, scores were reverse coded so that higher scores indicated higher QOL. 3,10,13 …”
Section: Quality Of Life Questionnaire and Transformed Scoresmentioning
confidence: 99%
“…3,10,13,19 For items with mixed or negative directionality, scores were reverse coded so that higher scores indicated higher QOL. 3,10,13 …”
Section: Quality Of Life Questionnaire and Transformed Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported in 2008 that women are interested in taking a leading role in the disclosure of perinatally acquired HIV infection to children and youth ages 5 to 18 years [14]. The possible parental concern that disclosure could interfere with Julio's quality of life could have been discussed with reference to results from a study among children and adolescents with perinatally acquired HIV infection, which showed no statistically significant differences between pre-disclosure and post-disclosure quality of life [15].…”
Section: Commentarymentioning
confidence: 99%